Решите уравнение. Образец: х+0,7*(3,2х-0,6х) при х=0,1 х+0,7*(3,2х-0,6х)=х+2,24х-0,42х=3,42х-0,42х=2,82х Если х=0,1 то 2,82х=2,82*0,1=0,282 Уравнение: х-0,3*(2,7х-1,4х) при х=0,1
Решите уравнение. Образец: х+0,7*(3,2х-0,6х) при х=0,1 х+0,7*(3,2х-0,6х)=х+2,24х-0,42х=3,42х-0,42х=2,82х Если х=0,1 то 2,82х=2,82*0,1=0,282 Уравнение: х-0,3*(2,7х-1,4х) при х=0,1
Ответ(ы) на вопрос:
Гость
х-0,3*1,3х=х-0,39х=0,61х.при х=0,1: 0,61*0,1=0,061
Гость
х-0,3*(2,7х-1,4х)=x-0.3*1.3x=x-0.39x=0.61x
0.61x=0.61*0,1=0.061
Не нашли ответ?
Похожие вопросы